Supplementation with engineered Lactococcus lactis improves the folate status in deficient rats - Leblanc, Jean Guy Joseph (2010)
The aim of this study was to establish the bioavailability of different folates produced by engineered Lactococcus (L.) lactis strains using a rodent depletion-repletion bioassay. Research Methods & Procedures: Rats were fed a folate-deficient diet, which produces a reversible subclinical folate deficiency, supplemented with different L. lactis cultures which were added as the only source of folate. Three bacterial strains that over-expressed either the folC, folKE or folC+KE genes were used. These strains produce folates with different polyglutamyl tail lengths. The growth response of the rats and the concentration of folates in different organs and blood samples were monitored. Results: The folate produced by the engineered strains was able to compensate the folate depletion in the diet and showed similar bioavailability compared to commercial folic acid that is normally used for food fortification. Folate concentrations in organ and blood samples increased significantly in animals that received the folate producing strains compared to those that did not receive bacterial supplementation. Hematological studies also showed that the administration of the L. lactis strains was able to revert a partial megaloblastic anemia caused by folate deficiency. No significant differences were observed in bioavailability of folates containing different glutamyl tail lengths. Conclusions: To our knowledge, this is the first study that demonstrated that folates produced by engineered lactic acid bacteria represent a bioavailable source of this essential vitamin.